A study of the conditions that hinder the primary school teachers in the Panjab (India) from organizing and operating the schools as community centres and the suggestions to overcome them - Dhand, Jagiri Mal 1925- (s.n.], 1963)
This study presents the educational needs of the Panjab community, the activities through which teachers meet these needs, the factors which hinder teachers in their efforts to operate the various activities, and the suggestions to overcome these factors.